(untitled) (Research, Society and Development, 2020)
Therefore, from this perspective, the research is a systematic, qualitative and descriptive bibliographic review, which used as a criterion for selecting literature from the last 35 years about the contexts and impacts of sexual violence in adolescence, given from the goal of investigating what are the contributions of psychology to adolescents victims of sexual violence, as well as it explores its concepts, contexts and psychological consequences, considering psychology as a strong support network, capable of being an important tool in the construction of a safe and welcoming environment, as well as promoting the free expression of the victim regarding his sufferings and feelings caused by the violence and its treatments, suggesting, by the end, an alliance of psychological doing with some intervention by the public power, based on construction of public policies and practices to prevent and aware people, as well as to treat health and safety problems directed to subjects in situations of sexual violence of high vulnerability, like the adolescents in question.